Effectiveness and tolerability of bakuchiol (Psolarea corylifolia) as a dermal anti-aging modality: A systematic review on skin wellness and harmony - Limanda, Claudia Felicia; Els, Vanessa; Hernowo, Elliana Freya; Winaya, Ketut Kwartantaya (Explorer Front, 2025)
Skin aging is a natural phenomenon caused by a decline in collagen production that leads to skin thinning, dry and pale skin, wrinkles, and sagging. Skin aging may not contribute to the mortality rate. However, people tend to connect their symbol of inner self to external appearance. Therefore, psychosocial effects such as social anxiety, low self-esteem, and low satisfaction in life will affect their personal and social life. Anti-aging procedures focus on the prevention of damage, replacement of tissues, and skin rejuvenation. Bakuchiol (Psolarea corylifolia) is a novel anti-aging product with antioxidant, anti-inflammatory, and anti-aging properties that is deemed effective and tolerable in skin rejuvenation. This comprehensive review aims to further examine the effectiveness and tolerability of bakuchiol based on previous studies in order to provide new insights into delaying skin aging. A comprehensive literature search was conducted to assess the effectiveness and tolerability of bakuchiol as a dermal anti-aging modality from search engines, PubMed, Google Scholar, CORE, Science Direct, and Cochrane using search terms (“Bakuchiol” OR “Psolarea corylifolia”) AND (“Dermal Aging” OR “Skin Aging”). Bakuchiol proved to have anti-inflammatory and antioxidant properties to maintain youthfulness and skin appearance. Regarding tolerability, bakuchiol has fewer side effects compared to other commonly used modalities. Therefore, bakuchiol (Psolarea corylifolia) is an effective and tolerable modality in the treatment of aging skin.